The potential of ornamental plant, Sansevieria trifasciata to inhibit the growth of Alexandrium tamiyavanichii, a toxic dinoflagellate - Ima Amirah binti Mohd Suberi (Kulliyyah of Science, International Islamic University Malaysia, 2017)
Harmful algal bloom (HAB) is a phenomenon that can cause harm to human health such as food poisoning and loss in aquaculture industries. However, in Malaysia, research on mitigation of HAB is very limited. This study aims to determine the potential of ornamental plant Sansevieria trifasciata in inhibiting the growth of HAB species, Alexandrium tamiyavanichii. The crude extracts and active fractions of this plant were tested on A. tamiyavanichii at different concentrations (0.001, 0.01, 0.1, 0.5, 1, 1.5, 2 and 2.5 mg/mL) for 24 hours. Toxicity test were conducted on artemia using different concentrations of crude extracts (10, 50, 100 mg/mL) and active fractions (10, 50, 100 and 500 mg/mL). Phytochemical screening was done to determine the constituents by using standard procedures. Results obtained showed that all concentration with different extracted method tested inhibited the growth of A. tamiyavanichii. As the concentration increase, the pH of medium will decrease and cause the removal efficiency to increase. The best removal efficiency was showed by methanol fraction from ethanol fresh plant extract which was 93.86% at concentration 0.1 mg/mL and pH 7.46. Artemia showed 100% mortality at concentration 50 mg/mL for ethanol fresh plant extract. For ethanol dried plant extract and distilled water fresh plant extract, 100% mortality of artemia was at 50 mg/mL while distilled water dried plant extract was at 100 mg/mL. All fractions showed 100% mortality of artemia at concentration 500 mg/mL. In phytochemical screening tests, compounds detected in ethanol fresh and dried plant extracts were alkaloid, tannins, glycoside, reducing sugar and terpenoids whereas in distilled water fresh and dried plant extract detected reducing sugar and terpenoids. For active fractions, all showed the presence of alkaloid, tannins, glycoside, reducing sugar and terpenoids. The compounds detected might have the function in inhibiting the targeted algae. Further study needed in order to determine the bioactivity and its effect on HABs' mitigation. This study showed that S. trifasciata has the potential to be used for mitigation of HAB particularly A. tamiyavanichii which help to minimize the impact of HAB in aquaculture field and human or animal health.